A case of ruptured infective coronary artery aneurysm - Kayo Sugiyama; Katsuhiko Matsuyama; Keita Maruno; Satoshi Takahashi; Masahiko Kuinose; Rena Nagashima; Hitoshi Ogino (Surgical Case Reports)
Abstract Infective coronary artery aneurysm is extremely rare and ruptured aneurysm is life-threatening. We report a case of ruptured coronary artery aneurysm, which was successfully treated by the patch closure technique and coronary artery bypass grafting. Pathological examination revealed purulent inflammation in the aneurysmal wall. Prompt diagnosis and appropriate treatment were essential.